PENGARUH PEMBERIAN JUS WORTEL TERHADAP PENURUNAN DERAJAT DISMENORE PADA REMAJA PUTRI - Isramilda; Ferry Daniel Martinus (Universitas Batam, 2022)
During menstruation, the most common complaint is menstrual pain or what is known as dysmenorrhea. Dysmenorrhea is characterized by lower abdominal pain. Ways how to overcome dysmenorrhea can be done by various treatments, one of them is drinking nutritious herbal drinks, namely carrot juice. Giving carrot juice contains vitamin E and beta-carotene which can provide analgesic and anti-inflammatory effects with the mechanism of action, namely inhibiting the activity enzymes and cyclooxygenase-2 enzymes so that these enzymes cannot convert arachidonic acid into prostaglandins as a cause of pain. Method: This research method is Pre-Experimental with One Group Pretest Post Test Design which was conducted at SMA Negeri 9 Pekanbaru in December 2021. The number of samples was 66 young women who were taken using the Simple Purposive Sampling technique. The result was analyzed by using the Dependent Sample T Test. Result: The result of the Dependent Sample T Test shows that there is an effect of giving carrot juice in decreasing the degree of dysmenorrhea of adolescent girls of SMA Negeri 9 Pekanbaru with a p- value of 0.000 < 0.05. Conclusion: Based on the result of this study, it can be conclude that there is reduction of the degree of dysmenorrhea of adolescent girls of SMA Negeri 9 Pekanbaru after giving carrot juices. It is highly recommended to respondents to consume carrot juices during menstruation so that it can decreases the discomfort they feel.